Cancer procoagulant (CP) in surgical oncology diagnostics - Szajda, Sławomir D.; Snarska, Jadwiga; Skrzydlewski, Zdzisław; Zwierz, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2005)
A considerable advancement of the neoplastic process at the start of the treatment is one of the major reasons of high mortality caused by malignant neoplasms. Numerous studies have been devoted to the diagnosis of cancer at its earliest stage, as the earliest administration of treatment tremendously increases chances of patients for total recovery. A considerable progress in oncological diagnostics has been observed since 1846, when the protein test of Bence-Jones was used in the diagnostics of multiple myeloma, for the first time. In the following decades, neoplastic markers were isolated and described. Since the discovery of carcinoembryonal antigen (CEA) and alpha – fetoprotein (AFP), which appeared to be a breakthrough in the research of neoplastic markers, determination of neoplastic markers has been introduced to the routine oncological diagnostics. At present, neoplastic markers, next to clinical examination and scanning (ultrasound, computed tomography, and magnetic resonance imaging) play an important role in detecting and monitoring malignant neoplasms. A significant increase of CP activity in the serum (in comparison to healthy persons) was found in many cancers of the gastrointestinal tract (oesophagus, stomach, liver, pancreas, colon) and the thyroid. The results of our own and other studies, show that examination of the CP activity could be used as a marker in oncological diagnostics.